The Effect of Social Support from Peers on the Mental Health of Seventh Grade Students at UPTD SMPN 16 Kota Kupang in the 2024/2025 Academic Year - Maria Dasilva Fallo; Rosa Mustika Bulor; Gracianus E. T. P Lejap (Universitas Muhammadiyah Enrekang, 2025)
The aim of this research is to determine the effect of peer social support on the mental health of students at SMPN 16 Kupang City for the 2024/2025 academic year. This type of research is quantitative research with a quantitative descriptive approach. The population in this study were students in class VII A, B, C, D, E, and F, totaling 172 students and the research sample was 42 students. The sampling technique is a purposive sampling technique. The data collection tool is a questionnaire. The research data analysis technique is simple linear regression. The results of this study show that the tcount value is greater than ttable (-4.231 > 0.312) and the significance value is 0.003 < 0.05. The results of this research data analysis show that there is an influence of peer social support on the mental health of class VII students at UPTD SMPN 16 Kupang City for the 2024/2025 academic year.